The Earth Charter, ecological integrity and social movements
1 online resource (xxxix, 250 pages)
Keywords: "The Earth Charter is a declaration of fundamental ethical principles for building a just, sustainable and peaceful global society, with ecological integrity as a major theme. This book provides a series of analyses of ecological integrity as it relates to the Earth Charter, social movements and international law for human rights. It is shown how the Earth Charter project began as a United Nations initiative, but it was carried forward and completed by a global civil society initiative. The book also shows the strong connection between ecological integrity and social justice, particularly in the defence of indigenous people, and includes contributions from both the North and the global South, specifically from Central and South America"--